2011
DOI: 10.1007/s13365-011-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of neuropathophysiology using diffusion-weighted magnetic resonance imaging in asymptomatic cats with feline immunodeficiency viral infection

Abstract: HIV infection results in a highly prevalent syndrome of cognitive and motor disorders designated as HIV-associated dementia (HAD). Neurologic dysfunction resembling HAD has been documented in cats infected with strain PPR of the feline immunodeficiency virus (FIV), whereas another highly pathogenic strain (C36) has not been known to cause neurologic signs. Animals experimentally infected with equivalent doses of FIV-C36 or FIV-PPR, and uninfected controls were evaluated by magnetic resonance diffusion-weighted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
1
5
2
Order By: Relevance
“…Neuroimaging results from MRI did not produce any significant differences in regard to brain diffusion. This is contrary to findings from a previous study that revealed increased brain diffusion in both PPR and C36-infected cats (Bucy et al, 2010). …”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Neuroimaging results from MRI did not produce any significant differences in regard to brain diffusion. This is contrary to findings from a previous study that revealed increased brain diffusion in both PPR and C36-infected cats (Bucy et al, 2010). …”
Section: Resultscontrasting
confidence: 99%
“…Images were obtained with cats under general anesthesia maintained with isoflurane gas via a non-rebreathing circuit and positive pressure ventilation. MRI and DW-MRI were performed as previously described (Bucy et al, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…Archived blood cell DNA from specific-pathogen-free domestic cats was obtained from three previous studies (22)(23)(24). BoHV4 and feline herpesvirus 1 (FeHV1) DNAs were extracted from infected cell culture supernatants (provided by Hana Van Campen and Sandra Quackenbush, respectively, both of Colorado State University) using a QIAamp DNA blood kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…Anatomic brain magnetic resonance imaging (MRI) scans, including proton density, T2-weighted, fluid attenuated inversion recovery (FLAIR), and T1-weighted (pre-and postcontrast) scans were performed on 10 i.c.-inoculated cats: 6 clinically ill (1 primary passage, 5 secondary passage), 2 asymptomatic (primary passage), and 2 age-matched sham controls, as well as 1 uninoculated age-matched control. MRI was done with a Signa LX 1.5 T MR HiSpeed Plus system (General Electric), as previously described (29). Briefly, anesthetized cats were positioned sternally with the head centered within the quadrature head coil.…”
Section: Domestic Cats Genotyping and Prion Protein Sequence Comparmentioning
confidence: 99%